CHIRAL PHOTONIC STRUCTURES WITH ANISOTROPIC DEFECT CONTROLLED BY HYDRODYNAMIC FLOW - R. B. Alaverdyan; T. K. Dadalyan
For the first time it is experimentally shown the possibility of planar defect induction in chiral liquid crystalline plane structure by means of hydrodynamic flow. The behavior of unpolarized light reflection spectrum from chiral liquid crystalline plane structure with planar defect induced by hydrodynamic flow is studied. The possible applications of observed phenomena are discussed.
Keywords: Physics; Optics